2017
DOI: 10.3945/cdn.117.001297
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Nutrition Care Process in US Hospitals Using a Web-Based Tool Demonstrates the Need for Quality Improvement in Malnutrition Diagnosis and Discharge Care

Abstract: Background: Malnutrition in hospitalized patients is a pervasive problem in the United States. To our knowledge, although malnutrition has been acknowledged as a concern for >40 y, it has not yet been well addressed with a systematic, process improvement approach. Objectives: We aimed to characterize the current nutrition care process in US hospitals to establish a baseline for improvements. We also aimed to demonstrate the application of a web-based quality improvement tool as a simple approach to address mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
1
14
0
3
Order By: Relevance
“…WHICH has been defined through an etiology-based approach and can include individuals who are underweight or overweight, 1 is a leading cause of morbidity and mortality, especially among older adults. 2,3 As many as half of all patients are malnourished or are at risk of becoming malnourished at the time of hospital admission, [4][5][6] with older adults especially at risk, often because of the health, physiologic, and functional changes associated with aging that can influence their nutritional status. 7,8 Early identification and treatment of these patients is the most effective way to reduce malnutrition-associated safety and health outcome issues.…”
Section: Alnutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…WHICH has been defined through an etiology-based approach and can include individuals who are underweight or overweight, 1 is a leading cause of morbidity and mortality, especially among older adults. 2,3 As many as half of all patients are malnourished or are at risk of becoming malnourished at the time of hospital admission, [4][5][6] with older adults especially at risk, often because of the health, physiologic, and functional changes associated with aging that can influence their nutritional status. 7,8 Early identification and treatment of these patients is the most effective way to reduce malnutrition-associated safety and health outcome issues.…”
Section: Alnutritionmentioning
confidence: 99%
“…In recent years, screening practices designed to detect patients at risk of malnutrition have become more widespread, and studies of their effectiveness have demonstrated that both patient health outcomes and hospital economic outcomes are improved when malnutrition is more effectively identified and treated. 6 Such malnutrition quality improvement (QI) efforts have ranged from taking basic steps for improving patient nutrition to implementing wide-sweeping overhauls of the entire process, including medical record reviews, tracking of nutrition supplement administration, and provision of enteral and parenteral nutrition support. 13-,15 In an effort to support hospitals seeking to implement malnutrition QI initiatives, the Malnutrition Quality Improvement Initiative (MQii) partners (Academy of Nutrition and Dietetics and Avalere Health) designed a toolkit (MQii Toolkit Team).…”
Section: Alnutritionmentioning
confidence: 99%
“…Aunque no forma parte del PAN, un requisito previo fundamental es realizar el cribaje nutricional para identificar a los P/C o grupos en riesgo que pueden beneficiarse de la valoración e intervención nutricional adicional 14,22,[35][36][37] .…”
Section: Descripción Del Modelo Y Proceso De Atención Nutricional Y Tunclassified
“…The variety of triggers of malnutrition in older adults has led to the development of tools for its early screening . These tools are increasingly used to screen for malnutrition at hospital admission . Yet, studies show that malnutrition is not resolved during hospitalization; rather, it deteriorates for up to 20% of patients, at least in part because of poor food intake …”
Section: Introductionmentioning
confidence: 99%